1995
DOI: 10.1007/bf00189339
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the geology of the Transvaal Sequence and Bushveld Complex, South Africa

Abstract: The Late Archaean-Early

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…feeder dykes are encountered throughout the basin. The deposition of the Ventersdorp Supergroup started at least 2729.2 ± 3.2 Ma ago (Poujol et al, 2005) and ended around 2642 ± 2 Ma (Eriksson et al, 1995) during the indentation stage between the Zimbabwe and Kaapvaal cratons. The overlaying sedimentary Transvaal Supergroup consists of dolomites from the lower Chuniespoort Group deposited between 2642 ± 2 Ma (Walraven and Martini, 1995) and 2432 ± 31 Ma and the volcano-sedimentary rocks of the upper Pretoria Group (maximum age of deposition, 2193 ± 20 Ma, Mapeo et al, 2006).…”
Section: Geological Settingmentioning
confidence: 99%
“…feeder dykes are encountered throughout the basin. The deposition of the Ventersdorp Supergroup started at least 2729.2 ± 3.2 Ma ago (Poujol et al, 2005) and ended around 2642 ± 2 Ma (Eriksson et al, 1995) during the indentation stage between the Zimbabwe and Kaapvaal cratons. The overlaying sedimentary Transvaal Supergroup consists of dolomites from the lower Chuniespoort Group deposited between 2642 ± 2 Ma (Walraven and Martini, 1995) and 2432 ± 31 Ma and the volcano-sedimentary rocks of the upper Pretoria Group (maximum age of deposition, 2193 ± 20 Ma, Mapeo et al, 2006).…”
Section: Geological Settingmentioning
confidence: 99%
“…In contrast to the many reported occurrences of Neoproterozoic glacial units and cap-carbonates, Paleoproterozoic glaciations are reported from only a few localities in North America (Young and Nesbitt, 1985), Europe (Marmo and Ojakangas, 1984;Strand and Laajoki, 1993), South Africa (Eriksson et al, 1995;Evans et al, 1997), and Australia (Trendall, 1976;Martin, 1999), and cap-carbonates are reported from only a few areas like the Espanola Formation of the Huronian Supergroup (Bekker et al, 2005), the Duitschland and Boshoek/Makganyene formations of the Transvaal Supergroup of South Africa (Bekker et al, 2001), and the Meteorite Bore Member of the Turee Creek Group (Martin, 1999;Lindsay and Brasier, 2002).…”
Section: Introductionmentioning
confidence: 74%
“…Two glacial diamictites have been reported from South African Paleoproterozoic rocks (Bekker et al, 2001;Frauenstein et al, 2009). The older one at the base of the Duitschland (2316 ± 7 Ma; 2424 ± 12 Ma) and the Timeball Hill (2324 ± 7 Ma) formations occurs above the 2431 ± 31 Ma Kuruman Formation (Lower Transvaal Group) (Eriksson et al, 1994(Eriksson et al, , 1995Mapeo et al, 2006;Kopp et al, 2005;Frauenstein et al, 2009). The younger Makganyene/Boshoek (2249 ± 6 Ma) glaciogenic formations are overlain by Ongeluk/Hekpoort lavas (2222 ± 12 Ma) and banded iron/manganese formations (Evans et al, 1997;Frauenstein et al, 2009).…”
Section: Importance For Global Correlation Of Paleoproterozoic Cap Camentioning
confidence: 96%
“…The rocks in the study area belong to the Timeball Hill Formation, which is located towards the base of the Pretoria Group, Transvaal Supergroup (Eriksson et al, 1995). The Pretoria Group, considered to be about 2.35-2.25 Ga in age (Walraven et al, 1990;Martin et al, 1998) comprises a generally upwardcoarsening 4000 m thick sequence of marine shelf shales, siltstones and sandstones.…”
Section: Geological Settingmentioning
confidence: 99%